The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11192-010-0280-y
|View full text |Cite|
|
Sign up to set email alerts
|

On using the Shanghai ranking to assess the research performance of university systems

Abstract: We take a new look at the Shanghai Jiao Tong Academic Ranking of World Universities to evaluate the performance of whole university systems. We deal with system aggregates by means of averaging scores taken over a number of institutions from each higher education system according to the Gross Domestic Product of its country. We treat the set of indicators (measures) at the country level as a scale, and investigate its reliability and dimensionality using appropriate statistical tools. After a Principal Compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 10 publications
3
49
1
13
Order By: Relevance
“…The position of universities in international rankings is today considered as a strategic issue for most universities. Although they begin as a tool to rank universities by comparing their research capacity and output, they are increasingly being used as a stick to measure institutions and not just in relation with research (Docampo 2011). However, there is a controversy regarding their methodologies and their choice of indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The position of universities in international rankings is today considered as a strategic issue for most universities. Although they begin as a tool to rank universities by comparing their research capacity and output, they are increasingly being used as a stick to measure institutions and not just in relation with research (Docampo 2011). However, there is a controversy regarding their methodologies and their choice of indicators.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used in the literature before to classify determinants of research productivity. See for instance Ramesh Babu and Singh (1998), Costas and Bordons (2007), Franceschet (2009), Docampo (2011), or Ortega, Lopez-Romero, and Fernandez (2011. Cordero-Ferrera, Pedraja-Chaparro, and Santín-González (2010) use PCA in a DEA framework to condense information.…”
Section: School Of International and Public Affairs And The Finance Amentioning
confidence: 99%
“…Hence, they concluded that criteria were random and depended on availability. the quantity and quality of its scientific production and the excellence of its students and alumni, the information it provides, when properly used, allows us to gain a useful insight into the research performance of whole university systems (Docampo, 2010 (Merisotis, 2002). Salmi and Saroyan (2007) examined league tables with their similarities and their potential to be used as information for policymakers and students.…”
Section: Controversies Around Global University Rankingsmentioning
confidence: 99%